Arthroscopic treatment for Morel-Lavallée lesion of the thigh: A case report and literature review. (January 2021) - Kage, Tomofumi; Hirota, Jinso; Yamamoto, Naoya; Kawasaki, Yosuke; Asai, Shin; Zhang, Liuzhe; Ugawa, Satomi; Seichi, Atsushi
Highlights: We present a case of Morel-Lavallée Lesion (MLL) of the thigh. The MLL was treated with arthroscopic procedure because of comorbidity. Negative pressure wound therapy was added to prevent recurrence. In case of MLL with comorbidity, the arthroscopic treatment is a reasonable method. Abstract: Introduction: Morel-Lavallée lesion (MLL) is a posttraumatic closed degloving soft tissue injury, in which the subcutaneous tissues are separated from the underlying fascia. Surgical treatment is recommended if conservative management fails. The conventional surgical treatment for the lesion is surgical drainage and debridement. Presentation of case: A 51-year-old male patient presented with swelling of the right thigh incurred during a traffic accident. The lesion was diagnosed with MLL. The MLL was successfully treated with a minimally invasive arthroscopic treatment after failure of conservative treatment. The arthroscopic treatment was chosen because of the patient's comorbidity that posed a risk of surgical wound complications. In addition, negative pressure wound therapy (NPWT) was performed postoperatively to ensure healing and to prevent recurrence of the lesion. The patient was successfully treated and the healing of the lesion was also confirmed with MRI. Discussion: In a patient with a risk of wound complications due to a comorbidity, this minimally invasive arthroscopic treatment is useful. In addition, NPWT was used to ensure healing and to prevent recurrence. Although the use of NPWT combined with endoscopic treatment has not been reported, additional NPWT reported in this case may be helpful to ensure healing. Conclusion: In case of MLL with a risk of surgical complications, the arthroscopic treatment is a reasonable method and achieves the goal of an open surgical debridement without increased morbidity.